Determinants of influenza vaccine uptake and willingness to be vaccinated by pharmacists among the active adult population in Hungary: a cross-sectional exploratory study - Githa Fungie Galistiani; Mária Matuz; Nikolett Matuszka; Péter Doró; Krisztina Schváb; Zsófia Engi; Ria Benkő (BMC, 2021)
Abstract Background Many studies have addressed influenza vaccine uptake in risk-group populations (e.g. the elderly). However, it is also necessary to assess influenza vaccine uptake in the active adult population, since they are considered to be a high-transmitter group. In several countries pharmacists are involved in adult vaccination in order to increase uptake. This study therefore aimed to investigate the determinants of influenza vaccination uptake and examine the willingness to be vaccinated by pharmacists. Methods A cross-sectional study was conducted among Hungarian adults using a self-administered online questionnaire distributed via social media (Facebook). The questionnaire included five domains: demographics, vaccine uptake, factors that motivated or discouraged vaccination, knowledge and willingness of participants to accept pharmacists as influenza vaccine administrators. Descriptive statistics were applied and logistic regression was conducted to assess the possible determinants of vaccination uptake. Results Data from 1631 participants who completed the questionnaires were analysed. Almost 58% of respondents (944/1631) had occupational and/or health risk factors for influenza. Just over one-tenth (12.3%;200/1631) of participants were vaccinated during the 2017/18 influenza season, 15.4% (145/944) of whom had a risk factor for influenza. Approximately half of the participants (47.4%) believed that influenza vaccination can cause flu, and just over half of them (51.6%), were not knowledgeable about the safety of influenza vaccine ingredients. Logistic regression found that age, sex, health risk factor and knowledge on influenza/influenza vaccination were associated with influenza vaccination uptake (p < 0.05). The most frequently cited reason for having an influenza vaccination was self-protection (95.0%). The most common reason given for refusing the influenza vaccine was that the respondent stated they rarely had an infectious disease (67.7%). The number of participants who were willing to be vaccinated by pharmacists was two-times higher than the number of participants who were actually vaccinated during the 2017/18 influenza season. Conclusion Influenza vaccine uptake in the active adult population is low in Hungary. Public awareness and knowledge about influenza vaccination and influenza disease should be increased. The results also suggest a need to extend the role played by pharmacists in Hungary.